HUBUNGAN PEMBELAJARAN KESEHATAN MATRA DENGAN KESIAPSIAGAAN MAHASISWA KEPERAWATAN FIKES UPN VETERAN JAKARTA DALAM PENANGGULANGAN BENCANA - Syaffira Putri Afifah, (2020)
Indonesia is one of the countries prone to disasters, therefore preparedness is important for students to do because students are a resource that must be trained in disaster management. Through the Matra Health course students are expected to be able to prepare for disaster management. The purpose of this study was to determine the Relationship of Learning Health Dimensions with Preparedness Disaster of Nursing Student FIKES UPN Veteran Jakarta in Disaster Management. The research method uses Mixed Methods with quantitative research using the Chi Square test and qualitative research using an open questionnaire. The population in this study were Nursing students of FIKES UPN Veterans Jakarta who had attended the Matra Health course both in terms of theory and practice of disaster simulation with a sample size of 122 respondents. The results of the quantitative approach in this study that there is a significant relationship between Matra Health Learning with Nursing Students Preparedness of FIKES UPN Veterans Jakarta in Disaster Management with test results (p = 0.004) (p = <0.05). While the results of the qualitative approach, that the importance of education about disasters so that students are able to make preparedness in disaster management